الدّيمقراطيّة الرّوحيّة: مراجعة لمقالة "الاجتهاد" عند محمّد إقبال: Spiritual Democracy: A Review of "al-ijtihad" Article by Muhammad Iqbal - حمدي رضا (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2016)
تبحث هذه الورقة في دعوة محمّد إقبال إلى إعادة الاعتبار لمبدأ الحركة في الفكر الإسلامي، بوصفه مبدأ قرآنيّاً أساسيّاً. ويعدّ الاجتهاد التجسيد الفعلي لمبدأ الحركة في مجال التفكير الفقهي. وقد لاحظ إقبال، في استعراضه لصفحات من تاريخ مفهوم الاجتهاد، أنّه كان الأداة المثلى لتجديد الفكر التشريعي الإسلامي. ويقتضي إحياء العمل بالاجتهاد اليوم إعادة النظر في مبادئ أصول الفقه وفروعه. وقد أدّاه النظر في فروع الأحكام الفقهية إلى الكشف عن ممكنات التجديد فيها، خاصّة في الجانبين السياسي والاجتماعي، وذهب في مراجعة الأصول إلى إبراز ما فيها من مرونة عالية، تؤهّلها لاستيعاب القضايا التي يواجهها المسلمون المعاصرون، والاجتهاد وحده كفيل بتحرير هذه الطاقات الإبداعية، لا لتجديد الفكر الإسلامي فحسب، بل لمعالجة أدواء الحضارة المعاصرة كذلك. This paper examines Muhammad Iqbal call to re-consider the principle of dynamics in Islamic thought, as a fundamental principle of Qur'an. Ijtihad is the actual embodiment of dynamism in the field of jurisprudent thinking. In his review of the history of ijtihad concept, Iqbal demonstrates that it was the perfect tool for the renewal of Islamic legislative thought. Furthermore, ijtihad revival the present requires a review of the principles of jurisprudence and its branches. Iqbal's review into these principles lead him to detect their renewal possibilities, especially in political and social aspects. Accordingly, he highlights the flexibility of these principles to cope with modern issues that Muslims face, and proclaims that Ijtihad alone guarantees to release the creative potentials, not only to renew Islamic thought, but also to address modern civilization problems as well.